Teaching reading to students with learning disabilities: Effects of combined iPad-assisted and peer-assisted instruction on oral reading fluency performance. Issue 6 (1st November 2020) - Mize, Min; Bryant, Diane P.; Bryant, Brian R.
ABSTRACT: Students with reading learning disabilities (RLDs) often face struggles in acquiring basic reading abilities, including oral reading fluency. The current study builds on previous work that compared peer-assisted instruction (PAI) to iPad-assisted instruction (IAI) on oral reading fluency, which led to the conclusion that a combined approach may be more effective than either approach alone. A multiple baseline design was used to examine the effectiveness of a combined PAI and IAI approach on oral reading fluency of four 5th grade students with RLD. Overall, there were moderate and positive experimental effects on oral reading fluency. Student gains were similar to expectations for typically achieving students from winter to spring.